بلاغة العتبات والشخوص في رواية أعالي الخوف لهزاع البراري: دراسة سردية - عبدالله، أماني سليمان داود (جامعة مؤتة - عمادة البحث العلمي, 2021)
تجتهد هذه الدراسة بالوقوف عند المحمولات الرؤيوية الكبرى التي تقدمها رواية "أعالي الخوف" للروائي الأردني هزاع البراري، وذلك بتأمل العتبات والشخوص على وجه الخصوص، ودراستهما بوصف الأولى منهما مفتتحاً بنيوياً لافتاً، وبوصف الثانية عنصراً مركزياً من عناصر الرواية، وكلاهما ينهض بالمعنى والدلالة التي يتقصدها الروائي؛ وقد افتتحت الرواية بعدة عتبات لافتة اشترك جلها في محاولة إيصال مقصد دلالي فكري محدد، كما رسمت الرواية لوحة لأبرز الشخصيات وأضاءت علاقاتها مع بعضها، إضافة إلى تداخل رؤاها وانفصالها، وارتباطها بسياقها الاجتماعي والديني والفكري وشرطها التاريخي الخاص وتفاعلها مع الزمان والمكان، لإنتاح الحدث الروائي ضمن حبكة ساهمت في تعزيز الرؤى الفكرية التي يحملها النص الروائي.
This study seeks to examine the major visionary implications presented by the novel “The Heights of Fear” by the Jordanian novelist Hazza Al-Barari.It contemplates and studies the text thresholds and characters of the novel in particular, the former as a striking structural opening, and the latter as a central element of the novel, while both of them give rise to the meaning and significance intended by the novelist. The novel opened with several remarkable thresholds, most of which participated in an attempt to convey a specific intellectual semantic aim. The novel also portrayed the most prominent characters and illuminated their relations with each other, in addition to the overlap of their visions, their separation, their connection to their social, religious and intellectual context, their special historical condition and their interaction with time and place. This helped to produce the narrative plot that contributed to strengthening the intellectual visions that the narrative text carries.
Keywords: الأدب العربي -- رواية أعالي الخوف -- البراري، هزاع -- النقد الأدبي